SCHOOL LIBRARY SERVICES AT UPT SMA NEGERI 5 ENREKANG DURING THE PANDEMIC PERIOD - Rita Afrianti; Syamsurijal Basri; Faridah Faridah (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The purpose of this study was to determine library services in this case circulation services, reference services, on-site reading services and ICT-based services as well as supporting and inhibiting factors in school library services. This research approach is qualitative with a type of description. Data collection techniques were carried out by interview, observation and documentations. Data analysis techniques using data reduction, data presentation and drawing conclusions. Checking the validity of the data is done by trianggulation technique. The reserch results showed that : 1) the circulation service has a collection of 19,839 books, but does not yet have a non-book collection such as tape recorders, sound slides, video cassettes, sound films and many more. The system used in this library is an open service system. 2) The reference service has 587 collections consisting of dictionaries, encyclopedias, maps and others. In this service, users can obtain information and assistance regarding the existence of the collection needed. 3) on-site reading services, in this service the library provides 6 reading tebles placed in several corners of the room so that students get good lighting and air circulation. Howefer, this service is currently unvailable because students rarely use it. 4) ICT-based services, in the SMA Negeri 5 Enrekang library this service is not yet available because officers are still in the stage of entering library materials into the library application. While the supporting factors for library services are the personnel or the staff themselves, staff commitment and adequate books. While the inhibiting factors are the library collections which are still in hard copy form, lack of student interest and limited staff/librarians.